Investigation of the factors that cause head injuries in pedestrian-scooter crashes - Lai, Shun Lai (Nanyang Technological University, 2021)
With the increase of usage of PMD in Singapore, the rate of accidents occurring are on the rise. The common cause of injury is from the rider falling from his or her PMD, severity of the injury may worsen if no protective equipment was used. In this report, the author will assess the severity of head injury via Head Injury Criterion (HIC) and using point clouds as a viable tool of measurement. Firstly, this is done by using the DTS Headsafe impactor. A drop test will be set-up to assess the factors affecting the HIC, being the drop height, impact velocity and the time interval. The data collector from the impactor is analysed via the TSR Control software. Secondly, the point clouds are recorded on an iPad Pro 2020 via the application SiteScape. The data collected from this project can used as the basis of accident reconstruction. Recommendations were given for further progress of this project.